The Burkholderia thailandensis Phages ΦE058 and ΦE067 Represent Distinct Prototypes of a New Subgroup of Temperate Burkholderia Myoviruses - Hammerl, Jens A.; Volkmar, Sven; Jacob, Daniela; Klein, Iris; Jäckel, Claudia; Hertwig, Stefan (Frontiers in Microbiology, 2020)
Burkholderia mallei and B. pseudomallei are highly pathogenic species which are closely related, but diverse regarding their prophage content. While temperate phages have not yet been isolated from B. mallei, several phages of B. pseudomallei and its non-pathogenic relative B. thailandensis have been described. In this study we isolated two phages from B. pseudomallei and three phages from B. thailandensis and determined their morphology, host range, and relationship. All five phages belong to the family Myoviridae, but some of them revealed different host specificities. DNA-DNA hybridization experiments indicated that the phages belong to two groups. One group, composed of ΦE058 (44,121 bp) and ΦE067 (43,649 bp), represents a new subgroup of Burkholderia myoviruses that is not related to known phages. The genomes of ΦE058 and ΦE067 are similar but also show some striking differences. Repressor proteins differ clearly allowing the phages to form plaques on hosts containing the respective other phage. The tail fiber proteins exhibited some minor deviations in the C-terminal region, which may account for the ability of ΦE058, but not ΦE067, to lyse B. mallei, B. pseudomallei and B. thailandensis. In addition, the integrases and attachment sites of the phages are not related. While ΦE058 integrates into the Burkholderia chromosome within an intergenic region, the ΦE067 prophage resides in the selC tRNA gene for selenocysteine. Experiments on the structure of phage DNA isolated from particles suggest that the ΦE058 and ΦE067 genomes have a circular conformation.